Telomere biology of trypanosomatids: beginning to answer some questions - Lira, Cristina B. B.; Giardini, Miriam A.; Neto, Jair L. Siqueira; Conte, Fabio F.; Cano, Maria Isabel N. (Elsevier B.V., 2007)
Studies of telomere structure and maintenance in trypanosomatids have provided insights into the evolutionary origin and conservation of some telomeric components shared by trypanosomes and vertebrates. For example, trypanosomatid telomeres are maintained by telomerase and consist of the canonical TTAGGG repeats, which in Trypanosoma brucei can form telomeric loops (t-loops). However, the telomeric chromatin of trypanosomatids is composed of organ ism-specific proteins and other proteins that share little sequence similarity with their vertebrate counterparts. Because telomere maintenance mechanisms are essential for genome stability, we propose that the particular features shown by the trypanosome telomeric chromatin hold the key for the design of antiparasitic drugs.